2023
DOI: 10.1136/gutjnl-2023-329685
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal syndromes preceding a diagnosis of Parkinson’s disease: testing Braak’s hypothesis using a nationwide database for comparison with Alzheimer’s disease and cerebrovascular diseases

Bo Konings,
Luisa Villatoro,
Jef Van den Eynde
et al.

Abstract: ObjectiveBraak’s hypothesis states that Parkinson’s disease (PD) originates in the gastrointestinal (GI) tract, and similar associations have been established for Alzheimer’s disease (AD) and cerebrovascular diseases (CVD). We aimed to determine the incidence of GI syndromes and interventions preceding PD compared with negative controls (NCs), AD and CVD.DesignWe performed a combined case-control and cohort study using TriNetX, a US based nationwide medical record network. Firstly, we compared subjects with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 53 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Consistent with prior studies 6 , our investigation did not establish a connection between GERD and PD, though there is well-documented relationship between GERD and MD, and we observed that GERD and PPI use was significantly higher in our MD cohort (Table 1). There are limitations utilizing ICD codes for GERD diagnosis, and likely some insufficiency of what is often now a clinical diagnosis of GERD based on symptoms and empiric response to PPI therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior studies 6 , our investigation did not establish a connection between GERD and PD, though there is well-documented relationship between GERD and MD, and we observed that GERD and PPI use was significantly higher in our MD cohort (Table 1). There are limitations utilizing ICD codes for GERD diagnosis, and likely some insufficiency of what is often now a clinical diagnosis of GERD based on symptoms and empiric response to PPI therapy.…”
Section: Discussionsupporting
confidence: 91%
“…However, the precise inciting factor triggering PD pathology in the gut remains elusive, complicating efforts to fully understand PD’s onset. A recent nationwide study found no association between a history of inflammatory bowel disease and subsequent risk of PD, suggesting that MD in the distal GI tract where pelvic rather than vagal innervation is the hallmark, may play a less important role in pathogenesis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The disease seems to originate in the gut in a subset of patients, and there is evidence of gastrointestinal syndromes preceding the diagnosis of Parkinson’s disease. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that serious infections (treated in hospital) of the gastrointestinal tract, but not all other sites, would be associated with a raised risk of Parkinson’s disease. The prodromal stage of Parkinson’s disease is notably variable in duration at the level of the individual, but is on average 10 years in the entire patient group, when some early gastrointestinal symptoms such as constipation, 3 , 11 dysphagia, gastroparesis and irritable bowel syndrome without diarrhoea occur. 3 Therefore, in this study, we considered age at infection to address possible bias due to reverse causation, where prodromal Parkinson’s disease activity may increase infection risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, PD manifests with a plethora of both motor and non-motor symptoms, many of which involve the gastrointestinal (GI) tract [6][7][8] . Among the latter, gastroparesis, gut inflammation, increased intestinal permeability, and constipation are frequently observed 8 and some of these GI symptoms have been shown to be predictive of PD 7 . Surprisingly, the GI tract involvement can precede motor symptoms by many years.…”
Section: Introductionmentioning
confidence: 99%